2016
DOI: 10.1016/j.ydbio.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

An Elk transcription factor is required for Runx-dependent survival signaling in the sea urchin embryo

Abstract: Elk proteins are Ets family transcription factors that regulate cell proliferation, survival, and differentiation in response to ERK (extracellular-signal regulated kinase)-mediated phosphorylation. Here we report the embryonic expression and function of Sp-Elk, the single Elk gene of the sea urchin Strongylocentrotus purpuratus. Sp-Elk is zygotically expressed throughout the embryo beginning at late cleavage stage, with peak expression occurring at blastula stage. Morpholino antisense-mediated knockdown of Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 108 publications
(127 reference statements)
0
7
0
Order By: Relevance
“…Knockdown studies have shown that Elk-1 effects transcription of several genes in the mouse brain and is considered a pro-differentiation factor there [25]. In the sea urchin S. purpuratus , elk has been shown to suppress apoptosis and promote cell proliferation in the early embryo [26]. Lv - elk is expressed at 10–18 hpf in the skeletogenic mesoderm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Knockdown studies have shown that Elk-1 effects transcription of several genes in the mouse brain and is considered a pro-differentiation factor there [25]. In the sea urchin S. purpuratus , elk has been shown to suppress apoptosis and promote cell proliferation in the early embryo [26]. Lv - elk is expressed at 10–18 hpf in the skeletogenic mesoderm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ETS family of genes is evolutionarily conserved [42,43,46,47] and formed by transcriptional regulators involved in various aspects of development, differentiation, hormone responses and tumorgenesis [4,4855]. Our genome wide survey of ETS transcription factors present in Nematostella revealed the presence of 12 members of this gene family (Fig S1).…”
Section: Discussionmentioning
confidence: 96%
“…; Rizzo et al . ). Quenching of translation‐blocking MASO was accomplished by annealing the quenching sense photomorpholino AAATGGCTGGAPGAAAAGCTG (P stands for photosensitive moiety) at a 1.1:1 concentration ratio to the antisense morpholino, following a previously established approach (Tallafuss et al .…”
Section: Methodsmentioning
confidence: 97%
“…The possibility of unintended splicing disruption by the translation-blocking MASO is also very low, because the highest contiguous similarity after scanning the genome is 18 bp and intergenic. Standard 3 0 -fluorescein-labeled morpholino CCTCTTACCT-CAGTTACAATTTATA was used as a negative control; this standard control morpholino has been previously tested by multiple researchers to determine the generic morpholino dose causing non-specific effects (Arenas-Mena et al 2006;Ooka et al 2010;Rizzo et al 2016). Quenching of translation-blocking MASO was accomplished by annealing the quenching sense photomorpholino AAATGGCTGGAPGAAAAGCTG (P stands for photosensitive moiety) at a 1.1:1 concentration ratio to the antisense morpholino, following a previously established approach (Tallafuss et al 2012).…”
Section: Downregulation Of H2az Expressionmentioning
confidence: 99%